Predictive brain activity related to auditory information is associated with performance in speech comprehension tasks in noisy environments - Okamoto, Kazuhiro; Hoyano, Kengo; Saiki, Yoshitomo; Nomura, Tomomi; Irie, Keisuke; Obama, Naoya; Kodama, Narihiro; Kobayashi, Yasutaka (Frontiers in Human Neuroscience, 2024)
IntroductionUnderstanding speech in noisy environments is challenging even for individuals with normal hearing, and it poses a significant challenge for those with hearing impairments or listening difficulties. There are limitations associated with the current methods of evaluating speech comprehension in such environments, especially in individuals with peripheral hearing impairments. According to the predictive coding model, speech comprehension is an active inference process that integrates sensory information through the interaction of bottom-up and top-down processing. Therefore, in this study, we aimed to examine the role of prediction in speech comprehension using an electrophysiological marker of anticipation: stimulus-preceding negativity (SPN).MethodsWe measured SPN amplitude in young adults with normal hearing during a time-estimation task with auditory feedback under both quiet and noisy conditions.ResultsThe results showed that SPN amplitude significantly increased in noisy environments. Moreover, individual differences in SPN amplitude correlated with performance in a speech-in-noise test.DiscussionThe increase in SPN amplitude was interpreted as reflecting the increased requirement for attentional resources for accurate prediction of speech information. These findings suggest that SPN could serve as a noninvasive neural marker for assessing individual differences in top-down processing involved in speech comprehension in noisy environments.